Health promotion interventions and policies addressing excessive alcohol use: a systematic review of national and global evidence as a guide to health‐care reform in China. (January 2015) - Li, Qing; Babor, Thomas F.; Zeigler, Donald; Xuan, Ziming; Morisky, Donald; Hovell, Melbourne F.; Nelson, Toben F.; Shen, Weixing; Li, Bing
Abstract: Aims: Steady increases in alcohol consumption and related problems are likely to accompany China's rapid epidemiological transition and profit‐based marketing activities. We reviewed research on health promotion interventions and policies to address excessive drinking and to guide health‐care reform. Methods: We searched Chinese‐ and English‐language databases and included 21 studies in China published between 1980 and 2013 that covered each policy area from the World Health Organization (WHO) Global Strategy to Reduce the Harmful Use of Alcohol. We evaluated and compared preventive interventions to the global alcohol literature for cross‐national applicability. Results: In contrast with hundreds of studies in the global literature, 11 of 12 studies from mainland China were published in Chinese; six of 10 in English were on taxation from Taiwan or Hong Kong. Most studies demonstrated effectiveness in reducing excessive drinking, and some reported the reduction of health problems. Seven were randomized controlled trials. Studies targeted schools, drink‐driving, work‐places, the health sector and taxation. Conclusions: China is the world's largest alcohol market, yet there has been little growth in alcohol policy research related to health promotion interventions over the past decade. Guided by a public health approach, the WHO Global Strategy and health reform experience in Russia, Australia, Mexico and the United States, China could improve its public health response through better coordination and implementation of surveillance and evidence‐based research, and through programmatic and legal responses such as public health law research, screening and early intervention within health systems and the implementation of effective alcohol control strategies.